Effects of methyl salicylate pre-treatment on the volatile profiles and key gene expressions in tomatoes stored at low temperature - Zeng, Xiangquan; Wang, Libin; Fu, Yingli; Zuo, Jinhua; Li, Yan; Zhao, Jingling; Cao, Rui; Li, Jian (Frontiers in Nutrition, 2022)
TTomato is one of the most widely cultivated horticultural plants in the world, while the key volatile compounds of tomato fruits generally derive from fatty acid, carotenoid, phenylalanine and branched-chain amino acid pathways. As an important endogenous signal molecule, methyl salicylate (MeSA) plays a crucial role in the fruit ripening process of plant. Recently, it has been demonstrated that MeSA can maintain the flavor quality of full ripe tomatoes after cold-storage preservation. However, few research teams attempted to investigate the effects of MeSA plus low temperature treatment on the different volatile biosynthetic pathways of tomatoes previously. Therefore, in this study, the effects of methyl salicylate pre-treatment (0.05 mM MeSA, 24 h) on the volatile profile and flavor-related key gene expressions of tomato fruits stored at 10 ℃ were evaluated for the first time. Our results showed that the loss of volatile compounds in low temperature-treated tomato fruits could be effectively alleviated by MeSA pre-treatment. Although MeSA had no remarkable effect on the formation of carotenoid pathway- and branched-chain amino acid pathway-related volatiles in tomatoes subjected to low temperature, the content of fatty acid pathway-related volatiles (including cis-3-hexenal, hexanal and trans-2-hexenal) in full red fruits of 10 ℃ MeSA group was remarkably higher than that of 10 ℃ control group. Furthermore, MeSA pre-treatment significantly up-regulated the expression of LOXC or LOXD gene in low temperature-treated fruits at breaker or full red stage, respectively. In conclusion, pre-treatment with MeSA might avoid the loss of aromatic compounds in tomato fruits stored at low temperature by activating the fatty acid pathway.